2010
DOI: 10.3174/ajnr.a2102
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abnormalities on MR Imaging in Patients with Retinoblastoma

Abstract: BACKGROUND AND PURPOSE:Although pineoblastoma is the main brain abnormality associated with hereditary retinoblastoma, recent studies suggest an association with pineal cysts. This association is important because some pineoblastomas mimic pineal cysts. If there is a relationship, then radiologists should be aware of it because diagnostic confusion is possible. Mental retardation and congenital brain anomalies are also reported in patients with retinoblastoma, mostly in combination with 13q deletion syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Moreover, KO mouse models have revealed the role of RB during neuronal differentiation and migration, as well as in the regulation of cell death in the embryo and adult brain (Andrusiak et al, 2011;Ghanem et al, 2012;McClellan et al, 2007;Christie et al, 2014;Ferguson et al, 2005;Macleod et al, 1996;Vandenbosch et al, 2016;Yu et al, 2012). The finding that lack of the RB1 gene is associated with structural brain abnormalities in human (Mitter et al, 2011;Rodjan et al, 2010), and inactivation of RB family proteins affects cell cycle and cell death in human ESCs (Conklin et al, 2012), suggest that RB might have a role during human brain development. However, the function of RB function in human development is still a mystery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, KO mouse models have revealed the role of RB during neuronal differentiation and migration, as well as in the regulation of cell death in the embryo and adult brain (Andrusiak et al, 2011;Ghanem et al, 2012;McClellan et al, 2007;Christie et al, 2014;Ferguson et al, 2005;Macleod et al, 1996;Vandenbosch et al, 2016;Yu et al, 2012). The finding that lack of the RB1 gene is associated with structural brain abnormalities in human (Mitter et al, 2011;Rodjan et al, 2010), and inactivation of RB family proteins affects cell cycle and cell death in human ESCs (Conklin et al, 2012), suggest that RB might have a role during human brain development. However, the function of RB function in human development is still a mystery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of neuronal morphology in Tuj1 + cells within KO teratomas, this result supports the role of RB in proper cell migration during human brain development. This ectopic migration, in addition to the cell proliferation increase mentioned above, could explain the macrocephaly described in individuals who lack RB (Mitter et al, 2011;Rodjan et al, 2010). Clearly, more questions remain, such as whether VLDLR is strictly required for the ectopic migration observed in RB1-KO organoids.…”
Section: Effect Of Rb In Neuronal Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Corpus callosum hypoplasia has also been reported in two patients with deletions 13q13.1q21.1 and 13q14.11q31.1 mapped by array CGH. 14 In the study by Rodjan et al, 37 MRI scan in seven patients with a 13q deletion showed corpus callosum agenesis in one patient and a Dandy-Walker variant in another patient, but locations of the deletions were not reported. Ballarati et al 13 and Kirchhoff et al 30 refined the region 13q32.3q33.1 as a critical region for corpus callosum agenesis but no specific candidate gene was found.…”
mentioning
confidence: 99%
“…Conditional knockout mice revealed pRb roles in neural migration and neurogenesis during development and adulthood (Andrusiak et al., 2011, Ghanem et al., 2012). In humans, deletions in chromosome 13q including RB1 were associated with brain abnormalities (Mitter et al., 2011, Rodjan et al., 2010), suggesting that it can play a role in human nervous system development.…”
Section: Introductionmentioning
confidence: 99%